International expansion plan of Softfinança - Wessel, Simon (2022)
The following document answers where Soft Finança (SF), a Portuguese software development company, should expand its product, “Soft Payments. ”With Covid-19 increasing adoption of digital financing, many may assume that most global markets could provide the company with immense opportunities. However, to truly identify a suitable market, the report conducts an internal and market assessment to understand the firm’s current situation and potential. With this information, a joint venture expansion into Luxembourg was identified as having the highest potential for SF, while a marketing analysis found that targeting affluent families would lead to the highest returns.